Selection into leadership and dishonest behavior of leaders: A gender experiment - Kerstin Grosch; Stephan Müller; Holger A. Rau; Lilia Zhurakhovska (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2020)
Leaders often have to weigh ethical against monetary consequences. Such situations may evoke psychological costs from being dishonest and dismissing higher monetary benefits for others. In a within-subjects experiment, we analyze such a dilemma. We first measure individual dishonest behavior when subjects report the outcome of a die roll, which determines their payoffs. Subsequently, they act as leaders and report payoffs for a group including themselves. In our main treatment, subjects can apply for leadership, whereas in the control treatment, we assign leadership randomly. Results reveal that women behave more dishonestly as leaders while men behave similarly in both the individual and the group decision. For female leaders, we find that sorting into leadership is not related to individual honesty preferences. In the control we find that female leaders do not increase dishonesty. A followup study reveals that female leaders become more dishonest after assuming leadership, as they align dishonest behavior with their belief on group members' honesty preferences.
Keywords: C91; H26; J16; 330; leadership; decision for others; lab experiment; gender differences; dishonesty